Does Institutional Ownership Moderate the Relationship Between the Board of Directors and Risk Disclosure? - Dhea Vania Dominique Pijoh; Bima Cinintya Pratama; Hadi Pramono; Ira Hapsari (Jurnal Akademi Akuntansi, 2022)
The purpose of this study is to dissect the ways in which institutional ownership, the number of years a board has been in operation, and the representation of women on the board each influence the strength of the association between risk disclosure and other parameters. Purposive sampling was utilized to collect data from commercial banks registered with OJK between 2017 and 2021. From 41 different locations, 205 samples were taken. To test their hypothesis, the researchers used a panel data regression model. Several different types of descriptive and inferential statistics tests were utilized in this investigation, including but not limited to likelihood, Breusch-Pagan, and Hausman tests, as well as tests for heteroscedasticity and autocorrelation. We utilize the fixed effect model to analyze the correlation between the variables in Regression Models 1 and 2 based on the results of the aforementioned three preliminary tests for the panel data regression model. According to the data, the presence of female board members has no influence on risk disclosure, but the length of time a board has been in existence and institutional ownership both positively increase risk disclosure. Risk disclosure is linked to board tenure and gender parity, although it is unclear how much of an effect institutional ownership characteristics have on this correlation. The study's goal is to clarify the role that shareholders play on corporate boards. To better use shareholder responsibilities, especially institutional ownership, by companies.